Core-shell structure hybrid particle, anti-corrosion wear-resistant coating and preparation method and application of anti-corrosion wear-resistant coating
By constructing an organic polymer transition layer on the surface of polytetrafluoroethylene and wrapping a two-dimensional sheet material, forming core-shell structure hybrid particles, and preparing the coating with an aqueous resin system, the problem of insufficient anti-corrosion performance of the coating in deep-sea environment is solved. Significantly improves corrosion and wear resistance.
Patent Information
- Application Number
- CN202411332391.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The corrosion resistance of metal coatings under high pressure and alternating pressure in existing deep-sea environments is insufficient, resulting in corrosive media penetration and interface performance deterioration, affecting the long-term corrosion resistance life of the composite coating.
The organic polymer transition layer was constructed on the surface of polytetrafluoroethylene by soapless emulsion polymerization, and wrapped it with the two-dimensional sheet material through hydrogen bonding to form core-shell structure hybrid particles, and the anti-corrosion and wear-resistant coating was prepared in combination with the aqueous resin system. .
It improves the density and physical shielding of the coating, enhances the corrosion resistance of the composite coating, extends the protection time, and reduces the friction coefficient and wear rate, significantly improving the corrosion resistance and wear resistance in deep-sea environments.
Smart Images

Figure CN119144019A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface protection, and specifically relates to a core-shell structure hybrid particle, an anticorrosion and wear-resistant coating, and a preparation method and application thereof. Background Art
[0002] The deep-sea environment is a harsh service environment, especially for metals. It is a highly corrosive environment. The hydrostatic pressure, oxygen concentration, light intensity, pH, temperature, salinity, flow rate and other conditions are very different from those in the shallow sea environment. The harsh deep-sea environment puts higher requirements on the coating protection technology used in it. The compatibility of nanofillers and polymer matrix directly determines the anti-corrosion performance of polymer composite coatings. Poor compatibility will lead to defects such as microcracks and holes between nanofillers and polymer matrix. During service, the high pressure in the deep sea will accelerate the infiltration, penetration and diffusion of corrosive media such as water molecules in the coating, eventually causing the coating to lose its protective performance. Moreover, the "push-pull" effect of alternating pressure will accelerate the destruction of the interface performance of the coating, thereby aggravating the damage and failure of metal materials. The strong hydrophobic effect of polytetrafluoroethylene and the "maze effect" of two-dimensional sheet materials can effectively reduce the infiltration, penetration and erosion of water molecules, that is, improve the barrier performance of the coating and enhance the protective effect of the polymer composite coating in the deep sea environment. However, as a nanofiller with low surface energy and poor adhesion, the addition of PTFE will lead to poor filler / waterborne resin interface performance. Corrosive media can easily penetrate the coating through the interfacial gap to the steel substrate, which can easily cause the coating to bubble and fall off, seriously affecting the long-term anti-corrosion life of the composite coating in deep-sea environments. Therefore, it is an urgent problem to provide a strong interface high-performance polytetrafluoroethylene modified composite coating for use in deep-sea environments. Summary of the invention
[0003] The main purpose of the present invention is to provide a core-shell structure hybrid particle, an anti-corrosion and wear-resistant coating and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.
[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: An embodiment of the present invention provides a core-shell structure hybrid particle, which includes: a polytetrafluoroethylene particle as a core, an organic polymer transition layer wrapped on the surface of the core, and a two-dimensional sheet material layer stacked on the surface of the organic polymer transition layer; wherein the two-dimensional sheet material layer is formed by a two-dimensional sheet material wrapped on the surface of the organic polymer transition layer at least through hydrogen bonding.
[0005] The present invention also provides a method for preparing the aforementioned core-shell structure hybrid particles, which comprises: The organic polymer transition layer is constructed on the surface of polytetrafluoroethylene by soap-free emulsion polymerization to obtain surface-activated polytetrafluoroethylene. Furthermore, the surface activated polytetrafluoroethylene is mixed with a two-dimensional sheet material to react and obtain core-shell structure hybrid particles.
[0006] The embodiment of the present invention also provides a method for preparing an anti-corrosion and wear-resistant coating, which comprises: uniformly mixing the core-shell structure hybrid particles with the water-based resin system, and then applying the obtained material to the surface of the metal substrate for curing treatment to obtain the anti-corrosion and wear-resistant coating; Wherein, the core-shell structure hybrid particles include the aforementioned core-shell structure hybrid particles.
[0007] The embodiment of the present invention also provides an anti-corrosion and wear-resistant coating prepared by the aforementioned preparation method.
[0008] The embodiments of the present invention also provide the application of the aforementioned core-shell structure hybrid particles or anti-corrosion and wear-resistant coating in the field of protection of marine engineering equipment serving in extreme deep-sea environments.
[0009] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention constructs an organic polymer transition layer on the surface of polytetrafluoroethylene by soap-free emulsion polymerization, and utilizes the hydrogen bonding between the two-dimensional sheet material and the organic polymer transition layer to prepare core-shell structured hybrid particles. This method can not only retain the hydrophobic effect of the polytetrafluoroethylene core, but also increase the surface active sites, improve the dispersibility and compatibility of polytetrafluoroethylene, and enhance the bonding force at the filler / resin interface; at the same time, the core-shell structured hybrid particles can effectively fill the microporous defects formed during the rapid curing process of the water-based resin, thereby improving the density and integrity of the coating; (2) Compared with polytetrafluoroethylene particles, the core-shell structure hybrid particles in the present invention can further improve the physical shielding effect of the composite coating. The corrosion protection performance of the core-shell structure hybrid particles prepared by compounding is significantly increased, the electrochemical impedance value is higher, and the protection time is longer; (3) The core-shell structured hybrid particles of the present invention can play a lubricating and anti-friction role, reduce the friction coefficient and wear rate of the composite coating, and greatly enhance the tribological properties of the composite coating; (4) The anti-corrosion and wear-resistant coating prepared by the present invention has excellent corrosion and wear resistance in harsh deep-sea environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0011] Figure 1a-1b The transmission electron microscope image of the core-shell structure hybrid particles and the image of the anti-corrosion and wear-resistant coating prepared in Example 1 of the present invention; Figure 2 This is the Bode diagram of the core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating prepared in Example 1 of the present invention in 3.5 wt.% NaCl solution; Figure 3 The Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 1 of the present invention under simulated ocean alternating pressure; Figure 4 This is a picture of the friction coefficient of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Examples 1, 2 and 3 of the present invention; Figure 5 The wear rate pictures of the core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coatings prepared in Examples 1, 2 and 3 of the present invention; Figure 6 This is a transmission electron microscopy image of the core-shell structure hybrid particles prepared in Example 2 of the present invention; Figure 7 The Bode diagram of the core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating prepared in Example 2 of the present invention in 3.5 wt.% NaCl solution; Figure 8 The Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 2 of the present invention under simulated ocean alternating pressure; Fig. 9 The Bode diagram of the core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating prepared in Example 3 of the present invention in 3.5 wt.% NaCl solution; Fig.10 This is the Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 3 of the present invention under simulated ocean alternating pressure; Fig.11 The Bode diagram of the anti-corrosion and wear-resistant coating prepared in Comparative Example 1 of the present invention under simulated ocean alternating pressure; Fig.12 This is the Bode diagram of the anti-corrosion and wear-resistant coating prepared in Comparative Example 2 of the present invention under simulated ocean alternating pressure; Fig.13 The Bode diagram of the anti-corrosion and wear-resistant coating prepared in Comparative Example 3 of the present invention under simulated ocean alternating pressure; Fig.14 The Bode diagram of the anti-corrosion and wear-resistant coating prepared in Comparative Example 4 of the present invention under simulated ocean alternating pressure; Fig.15 This is the Bode diagram of the anti-corrosion and wear-resistant coating prepared in comparative example 5 of the present invention under simulated ocean alternating pressure. DETAILED DESCRIPTION
[0012] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0013] Specifically, as one aspect of the technical solution of the present invention, a core-shell structure hybrid particle involved therein comprises: a polytetrafluoroethylene particle as a core, an organic polymer transition layer wrapped on the surface of the core, and a two-dimensional sheet material layer stacked on the surface of the organic polymer transition layer; wherein the two-dimensional sheet material layer is formed by a two-dimensional sheet material wrapped on the surface of the organic polymer transition layer at least through hydrogen bonding.
[0014] In some preferred embodiments, the particle size of the polytetrafluoroethylene particles is 100-500 nm.
[0015] In some preferred embodiments, the polytetrafluoroethylene particles are rod-shaped or elliptical.
[0016] In some preferred embodiments, the thickness of the organic polymer transition layer is 25-100 nm.
[0017] In some preferred embodiments, the two-dimensional sheet material includes graphene, GO, Ti3C2T x , MoS2, h-BN, LDHs, any one or more combinations thereof, but not limited thereto.
[0018] In some preferred embodiments, the two-dimensional sheet material has a sheet size of 50-250 nm.
[0019] In some preferred embodiments, the two-dimensional lamellar material includes a single-layer two-dimensional lamellar material and / or a few-layer two-dimensional lamellar material; wherein the few-layer two-dimensional lamellar material is a two-dimensional lamellar material with ≤10 layers.
[0020] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned core-shell structure hybrid particles, which comprises: The organic polymer transition layer is constructed on the surface of polytetrafluoroethylene by soap-free emulsion polymerization to obtain surface-activated polytetrafluoroethylene. Furthermore, the surface activated polytetrafluoroethylene is mixed with a two-dimensional sheet material to react and obtain core-shell structure hybrid particles.
[0021] In some preferred embodiments, the preparation method specifically comprises: Ultrasonic mixing of polytetrafluoroethylene emulsion and water to form polytetrafluoroethylene dispersion; Adding the polymerization monomer to the polytetrafluoroethylene dispersion, and dropping an initiator at 55-80° C. and stirring for 4-10 hours to obtain surface-activated polytetrafluoroethylene; Furthermore, the surface activated polytetrafluoroethylene is mixed with the two-dimensional sheet material and stirred at 25-60° C. for 12-36 hours to obtain core-shell structured hybrid particles.
[0022] Further, the polymerizable monomer includes any one or more combinations of methyl methacrylate, glycidyl methacrylate, acrylamide, styrene, ethyl acrylate, divinylbenzene, vinyl methoxysilane, and γ-methacryloxypropyltrimethoxysilane, but is not limited thereto.
[0023] Further, the initiator includes potassium sulfate and / or sodium persulfate, but is not limited thereto.
[0024] Furthermore, the groups on the surface of the surface activated polytetrafluoroethylene include any one or more combinations of hydroxyl groups, carboxyl groups, amino groups, benzene rings, carbonyl groups, ester groups, and epoxy groups, but are not limited thereto.
[0025] Furthermore, the content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 3-7 wt.%.
[0026] Furthermore, the mass ratio of the polytetrafluoroethylene dispersion to the polymerization monomer is 1:(1.5-3).
[0027] Furthermore, the mass ratio of the surface activated polytetrafluoroethylene to the two-dimensional sheet material is (3-5):1.
[0028] Furthermore, the dropping speed of the initiator is (20-50 s) / drop.
[0029] In some more specific embodiments, the method for preparing the core-shell structured hybrid particles specifically comprises: The polytetrafluoroethylene emulsion is ultrasonically mixed with deionized water at room temperature to obtain a pretreated polytetrafluoroethylene dispersion; a mixed solution of polymerization monomers is added to the pretreated polytetrafluoroethylene dispersion, wherein the mass ratio of methyl methacrylate, glycidyl methacrylate, acrylamide and styrene in the polymerization monomers is (3-6): (1-3): (0.5-3): (0.5-3); the mixture is ultrasonically treated for 10-30 minutes at room temperature, and nitrogen is passed for 10-20 minutes until the air is completely exhausted, and then the mixture is stirred in a 70°C oil bath for 5-15 minutes. After the reaction system is stable, an initiator is added dropwise, and the mixture is reacted at 55-80°C for 4-10 hours, cooled to room temperature, centrifuged at 1500-5000 r / min for 5-10 minutes, washed with deionized water and ethanol for 3 times, and freeze-dried to obtain surface-activated polytetrafluoroethylene.
[0030] 90-300 mg of surface-activated polytetrafluoroethylene and 30-60 mg of two-dimensional lamellar material are dispersed in deionized water respectively, and ultrasonic dispersion is performed for 30 min to obtain well-dispersed surface-activated polytetrafluoroethylene dispersion and two-dimensional lamellar material dispersion. The two dispersions are mixed and reacted in an oil bath at 50°C for 24 h. The mixed solution of the above reaction is centrifuged at 5000-8000 r / min for 3-15 min, the supernatant is removed, the precipitate is frozen and placed in a freeze dryer, and dried at -35°C for 10-20 h to obtain core-shell structured hybrid particles.
[0031] Another aspect of the embodiments of the present invention further provides a method for preparing an anti-corrosion and wear-resistant coating, which comprises: The core-shell structure hybrid particles are mixed evenly with a water-based resin system, and then the obtained material is applied to the surface of a metal substrate for curing to obtain an anti-corrosion and wear-resistant coating; Wherein, the core-shell structure hybrid particles include the aforementioned core-shell structure hybrid particles.
[0032] In some preferred embodiments, the curing temperature is 30-50°C.
[0033] In some preferred embodiments, the curing treatment time is 60 to 90 hours.
[0034] In some preferred embodiments, the mass ratio of the core-shell structure hybrid particles to the aqueous resin system is (0.2-2):100.
[0035] In some preferred embodiments, the water-based resin system includes a first component and a second component; wherein the first component includes a water-based resin and a dispersion, and the second component includes a water-based curing agent and a defoaming agent.
[0036] Further, the water-based resin includes any one or more combinations of MU-618, PLR 609B, AB-EP-20, and AB-FP-44, but is not limited thereto.
[0037] Furthermore, the dispersion liquid includes deionized water, ethanol, and methanol, but is not limited thereto.
[0038] Further, the water-based curing agent includes any one or more combinations of CU-600, PLR 736K, AB-HZ, and AB-HGA, but is not limited thereto.
[0039] Furthermore, the defoaming agent includes DT-69, DT-650, DU-966, DU-2198, Foamex 810, Airex901W, but is not limited thereto.
[0040] In some preferred embodiments, the metal substrate includes any one of carbon steel, stainless steel, aluminum alloy, and titanium alloy, but is not limited thereto.
[0041] In some preferred embodiments, the thickness of the anti-corrosion and wear-resistant coating is 20-100 μm.
[0042] Another aspect of the embodiments of the present invention further provides an anti-corrosion and wear-resistant coating prepared by the aforementioned preparation method.
[0043] The core-shell structured hybrid particles in the anti-corrosion and wear-resistant coating prepared by the present invention can effectively fill the micropore defects in the rapid curing process of the water-based resin, improve the density and physical shielding effect of the coating, and enhance the corrosion resistance of the coating in a deep-sea environment; at the same time, the addition of the core-shell structured hybrid particles can also effectively reduce the friction coefficient and wear rate of the coating, and improve the tribological properties of the coating.
[0044] Another aspect of the embodiments of the present invention further provides the application of the aforementioned core-shell structure hybrid particles or corrosion-resistant and wear-resistant coatings in the field of protection of marine engineering equipment serving in extreme deep-sea environments.
[0045] Furthermore, the application includes application in the surface protection of metal materials in harsh environments of high pressure, high humidity or high salt mist.
[0046] For example, the metal material includes any one of carbon steel, stainless steel, aluminum alloy, and titanium alloy.
[0047] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0048] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0049] Example 1 (1) Preparation of surface activated polytetrafluoroethylene 2 g of polytetrafluoroethylene emulsion was ultrasonically mixed with deionized water at room temperature for 30 min to obtain a pretreated polytetrafluoroethylene dispersion. 5 g of a mixture of polymerization monomers was added to the pretreated polytetrafluoroethylene dispersion, wherein the mass ratio of methyl methacrylate, glycidyl methacrylate, acrylamide, and styrene was 4:2:1:1, and ultrasonicated for 15 min at room temperature, and nitrogen was passed through the mixture for 15 min. After the air was completely discharged, it was slowly heated to 70 ° C under nitrogen protection and stirred for 10 min to obtain a stable mixed system. 0.4 wt.% potassium persulfate was added dropwise to the stable mixed system and reacted at 70 ° C for 6 h. Cooled to room temperature, centrifuged at 3500 r / min for 5 min, washed with deionized water and ethanol 3 times, and freeze-dried to obtain surface-activated polytetrafluoroethylene.
[0050] (2) Synthesis of core-shell hybrid particles First, 200 mg of surface-activated polytetrafluoroethylene and 50 mg of graphene oxide were dispersed in 20 ml of deionized water, and ultrasonically dispersed for 30 min to obtain well-dispersed surface-activated polytetrafluoroethylene dispersion and graphene oxide dispersion. The above two dispersions were mixed and reacted in an oil bath at 50 °C for 24 h. The mixed solution of the above reaction was centrifuged at 8000 r / min for 5 min, and the supernatant was removed. The precipitate was frozen and placed in a freeze dryer, and dried at -35 °C for 10 h to obtain core-shell structure hybrid particles. (3) Preparation of core-shell structured hybrid particles to enhance corrosion and wear resistant coatings 0.6 g of core-shell structure hybrid particles were added to deionized water for ultrasonic dispersion for 10 min, and then defoamed and excess solution was removed in a vacuum oven. 34 g of water-based epoxy resin was added and stirred in a mixer at 3500 r / min for 3 min to mix evenly, and then 17 g of water-based curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 72 h to form a core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating with a thickness of about 50 μm.
[0051] The transmission electron microscopy image of the core-shell structure hybrid particles prepared in Example 1 is as follows Figure 1a As shown in the picture of corrosion-resistant coating Figure 1b As shown; Figure 2This is the Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 1 in 3.5 wt.% NaCl solution; Figure 3 The Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 1 under simulated ocean alternating pressure; The friction coefficient diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 1 of the present invention is as follows: Figure 4 As shown; the wear rate of the core-shell structure hybrid particles reinforced anti-corrosion and wear-resistant coating prepared in Example 1 of the present invention is shown in Figure 5 shown.
[0052] Example 2 (1) Preparation of surface activated polytetrafluoroethylene 3 g of polytetrafluoroethylene emulsion was ultrasonically mixed with deionized water at room temperature for 30 min to obtain a pretreated polytetrafluoroethylene dispersion. 9 g of a mixture of polymerization monomers was added to the pretreated polytetrafluoroethylene dispersion, wherein the mass ratio of methyl methacrylate, ethyl acrylate, and acrylamide was 4:3:2, and the mixture was ultrasonically treated at room temperature for 20 min, and nitrogen was passed through the mixture for 15 min. After the air was completely discharged, it was slowly heated to 80 ° C under nitrogen protection and stirred for 15 min to obtain a stable mixed system. 0.4 wt.% potassium persulfate was added dropwise to the stable mixed system and reacted at 80 ° C for 5 h. Cooled to room temperature, centrifuged at 4000 r / min for 5 min, washed with deionized water and ethanol 3 times, and freeze-dried to obtain surface-activated polytetrafluoroethylene.
[0053] (2) Synthesis of core-shell hybrid particles First, 250 mg of surface-activated polytetrafluoroethylene and 50 mg of graphene oxide were dispersed in 20 ml of deionized water, and ultrasonically dispersed for 30 min to obtain well-dispersed surface-activated polytetrafluoroethylene dispersion and graphene oxide dispersion. The two dispersions were mixed and reacted in an oil bath at 50 °C for 24 h. The mixed solution of the above reaction was centrifuged at 8000 r / min for 5 min, and the supernatant was removed. The precipitate was frozen and placed in a freeze dryer, and dried at -35 °C for 12 h to obtain core-shell structure hybrid particles. (3) Preparation of core-shell structured hybrid particles to enhance corrosion and wear resistant coatings 0.3 g of core-shell structure hybrid particles were added to deionized water for ultrasonic dispersion for 10 min, and then defoamed and excess solution was removed in a vacuum oven. 40 g of water-based epoxy resin was added and stirred in a mixer at a speed of 3500 r / min for 5 min to mix evenly, and then 20 g of water-based curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 90 h to form a core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating with a thickness of about 30 μm.
[0054] The transmission electron microscopy image of the core-shell structure hybrid particles in Example 2 is as follows Figure 6 As shown; Figure 7 This is the Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 2 in 3.5 wt.% NaCl solution; Figure 8 The Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 2 under simulated ocean alternating pressure; The friction coefficient diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 2 of the present invention is as follows Figure 4 As shown; the wear rate of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 2 of the present invention is shown in Figure 5 shown.
[0055] Example 3 (1) Preparation of surface activated polytetrafluoroethylene 1 g of polytetrafluoroethylene emulsion was ultrasonically mixed with deionized water at room temperature for 20 min to obtain a pretreated polytetrafluoroethylene dispersion. 2 g of a mixture of polymerization monomers was added to the pretreated polytetrafluoroethylene dispersion, wherein the mass ratio of methyl methacrylate, styrene, vinylmethoxysilane, and divinylbenzene was 2:1:1:1, and ultrasonicated for 10 min at room temperature, and nitrogen was passed through the mixture for 15 min. After the air was completely discharged, it was slowly heated to 60 ° C under nitrogen protection and stirred for 15 min to obtain a stable mixed system. 0.4 wt.% sodium persulfate was added dropwise to the stable mixed system and reacted at 60 ° C for 9 h. Cooled to room temperature, centrifuged at 4000 r / min for 5 min, washed 3 times with deionized water and ethanol, and freeze-dried to obtain surface-activated polytetrafluoroethylene.
[0056] (2) Synthesis of core-shell hybrid particles First, 250 mg of surface activated polytetrafluoroethylene and 50 mg of Ti3C2T x They were dispersed in 20 ml of deionized water and ultrasonically dispersed for 30 min to obtain well-dispersed surface-activated polytetrafluoroethylene dispersion and Ti3C2T xDispersion. The above two dispersions were mixed and reacted in an oil bath at 50 °C for 24 h. The mixed solution of the above reaction was centrifuged at 8000 r / min for 5 min, and the supernatant was removed. The precipitate was frozen and placed in a freeze dryer, and dried at -35 °C for 12 h to obtain core-shell structure hybrid particles.
[0057] (3) Preparation of core-shell structured hybrid particles to enhance corrosion and wear resistant coatings 0.6 g of core-shell structure hybrid particles were added to deionized water for ultrasonic dispersion for 10 min, and then defoamed and excess solution was removed in a vacuum oven. 20 g of water-based epoxy resin was added and stirred in a mixer at 3500 r / min for 5 min to mix evenly, and then 10 g of water-based curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 90 h to form a core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating with a thickness of about 100 μm.
[0058] Fig. 9 is the Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 3 in 3.5 wt.% NaCl solution; Fig.10 The Bode diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 3 under simulated ocean alternating pressure; The friction coefficient diagram of the core-shell structure hybrid particle reinforced anti-corrosion and wear-resistant coating prepared in Example 3 of the present invention is as follows: Figure 4 As shown; the wear rate of the core-shell structure hybrid particles reinforced anti-corrosion and wear-resistant coating prepared in Example 3 of the present invention is shown in Figure 5 shown.
[0059] Comparative Example 1 The method is the same as in Example 1, except that a corresponding mass of polytetrafluoroethylene is used instead of the core-shell structure hybrid particles; specifically comprising: Preparation of polytetrafluoroethylene anticorrosion and wear-resistant coating: 0.6 g polytetrafluoroethylene was added to deionized water for ultrasonic dispersion for 15 min, and the excess solution was removed in a vacuum oven for defoaming. 34 g water-based epoxy resin was added, and the mixture was stirred in a mixer at a speed of 3500 r / min for 5 min to mix evenly, and then 17 g water-based curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 72 h to form a polytetrafluoroethylene-modified anticorrosion and wear-resistant coating with a thickness of about 50 μm.
[0060] Fig.11 This is the Bode diagram of the anti-corrosion and wear-resistant coating prepared in comparative example 1 under simulated ocean alternating pressure.
[0061] Comparative Example 2 The method is the same as in Example 1, except that graphene oxide is absent, and specifically comprises: (1) Preparation of surface activated polytetrafluoroethylene 1 g of polytetrafluoroethylene emulsion was ultrasonically mixed with deionized water at room temperature for 20 min to obtain a pretreated polytetrafluoroethylene dispersion. 2.5 g of a mixture of polymerization monomers was added to the pretreated polytetrafluoroethylene dispersion, wherein the mass ratio of methyl methacrylate, glycidyl methacrylate, acrylamide, and styrene was 4:2:1:1, and ultrasonicated for 15 min at room temperature, and nitrogen was passed through the mixture for 10 min. After the air was completely discharged, it was slowly heated to 70 ° C under nitrogen protection and stirred for 10 min to obtain a stable mixed system. 0.4 wt.% potassium persulfate was added dropwise to the stable mixed system and reacted at 70 ° C for 6 h. Cooled to room temperature, centrifuged at 3500 r / min for 5 min, washed 3 times with deionized water and ethanol, and freeze-dried to obtain surface-activated polytetrafluoroethylene.
[0062] (2) Preparation of surface activated polytetrafluoroethylene modified anti-corrosion and wear-resistant coating 0.3 g of surface activated polytetrafluoroethylene was added to deionized water and stirred for 20 min by ultrasonication, and then defoamed and excess solution was removed in a vacuum oven. 17 g of waterborne epoxy resin was added and stirred in a mixer at a speed of 3500 r / min for 3 min to mix evenly, and then 8.5 g of waterborne curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 72 h to form a surface activated polytetrafluoroethylene modified anticorrosion and wear-resistant coating with a thickness of about 50 μm.
[0063] Fig.12 This is the Bode diagram of the anti-corrosion and wear-resistant coating prepared in Comparative Example 2 under simulated ocean alternating pressure.
[0064] Comparative Example 3 The method is the same as in Example 1, except that a corresponding mass of graphene oxide is used instead of the core-shell structure hybrid particles, specifically comprising: 0.6 g of graphene oxide (sheet size of 50-200 nm) was added to deionized water and ultrasonically stirred for 20 min, and then defoamed and excess solution was removed in a vacuum oven. 34 g of water-based epoxy resin was added and stirred in a mixer at 3500 r / min for 3 min to mix evenly, and then 17 g of water-based curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 72 h to form a graphene oxide modified anticorrosion and wear-resistant coating with a thickness of about 50 μm.
[0065] Fig.13 This is the Bode diagram of the anti-corrosion and wear-resistant coating prepared in comparative example 3 under simulated ocean alternating pressure.
[0066] Comparative Example 4 The method is the same as in Example 2, except that an equal mass of a mixture of polytetrafluoroethylene and graphene oxide is used to replace the core-shell structure hybrid particles, specifically comprising: (1) Preparation of polytetrafluoroethylene and graphene oxide mixture 0.5 g of polytetrafluoroethylene and 0.5 g of graphene oxide dispersion were mixed and mixed in an oil bath at 50 °C for 24 h. The mixed solution of the above reaction was centrifuged at 8000 r / min for 5 min, and the supernatant was removed. The precipitate was frozen and placed in a freeze dryer and dried at -35 °C for 12 h to obtain a mixture of polytetrafluoroethylene and graphene oxide.
[0067] (2) Preparation of polytetrafluoroethylene and graphene oxide mixture to enhance corrosion and wear resistant coating 0.3 g of polytetrafluoroethylene and graphene oxide mixture was added to deionized water for ultrasonic dispersion for 10 min, and then defoamed and excess solution was removed in a vacuum oven. 40 g of water-based epoxy resin was added and stirred in a mixer at 3500 r / min for 5 min to mix evenly, and then 20 g of water-based curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 90 h to form a core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating with a thickness of about 30 μm.
[0068] Fig.14 This is the Bode diagram of the anti-corrosion and wear-resistant coating prepared in comparative example 4 under simulated ocean alternating pressure.
[0069] Comparative Example 5 The method is the same as in Example 3, except that a corresponding mass of a polymer transition layer without a polytetrafluoroethylene inner core is used instead of the core-shell structure hybrid particles, specifically comprising: (1) Preparation of polymer transition layer without polytetrafluoroethylene core 2 g of the mixed solution of polymer monomers was mixed with deionized water and added to a three-necked flask, wherein the mass ratio of methyl methacrylate, styrene, vinylmethoxysilane and divinylbenzene was 2:1:1:1, and ultrasonicated at room temperature for 10 min, and nitrogen was passed into the mixed solution for 15 min. After the air was completely discharged, it was slowly heated to 60 ° C under nitrogen protection and stirred for 15 min to obtain a stable mixed system. 0.4 wt.% sodium persulfate was added dropwise to the stable mixed system and reacted at 60 ° C for 9 h. Cooled to room temperature, centrifuged at 4000 r / min for 5 min, washed with deionized water and ethanol 3 times, and freeze-dried to obtain a polytetrafluoroethylene-free core polymer transition layer.
[0070] (2) Preparation of polymer transition layer reinforced anti-corrosion and wear-resistant coating without polytetrafluoroethylene core 0.6 g of the polymer transition layer without polytetrafluoroethylene core was added to deionized water for ultrasonic dispersion for 10 min, and then defoamed and excess solution was removed in a vacuum oven. 20 g of water-based epoxy resin was added and stirred in a mixer at a speed of 3500 r / min for 5 min to mix evenly, and then 10 g of water-based curing agent was added and stirred for 10 min. The defoaming process was performed again in a vacuum drying oven, and the obtained material was coated on carbon steel and cured at room temperature for 90 h to form a core-shell structure hybrid particle reinforced anticorrosion and wear-resistant coating with a thickness of about 100 μm.
[0071] Fig.15 This is the Bode diagram of the anti-corrosion and wear-resistant coating prepared in comparative example 5 under simulated ocean alternating pressure.
[0072] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0073] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A core-shell structure hybrid particle, characterized in that: include: A polytetrafluoroethylene particle as a core, an organic polymer transition layer wrapped on the surface of the core, and a two-dimensional sheet material layer stacked on the surface of the organic polymer transition layer; wherein the two-dimensional sheet material layer is formed by a two-dimensional sheet material wrapped on the surface of the organic polymer transition layer at least through hydrogen bonding.
2. The core-shell structure hybrid particle according to claim 1, characterized in that: The particle size of the polytetrafluoroethylene particles is 100-500 nm; and / or the polytetrafluoroethylene particles are rod-shaped or elliptical; And / or, the thickness of the organic polymer transition layer is 25-100 nm; And / or, the two-dimensional sheet material includes graphene, GO, Ti3C2T x , MoS2, h-BN, LDHs, any one or more combinations; And / or, the sheet diameter of the two-dimensional sheet material is 50-250 nm; And / or, the two-dimensional lamellar material includes a single-layer two-dimensional lamellar material and / or a few-layer two-dimensional lamellar material; wherein the few-layer two-dimensional lamellar material is a two-dimensional lamellar material with ≤10 layers.
3. The method for preparing the core-shell structure hybrid particles according to claim 1 or 2, characterized in that: include: The organic polymer transition layer is constructed on the surface of polytetrafluoroethylene by soap-free emulsion polymerization to obtain surface-activated polytetrafluoroethylene. Furthermore, the surface activated polytetrafluoroethylene is mixed with a two-dimensional sheet material to react and obtain core-shell structure hybrid particles.
4. The preparation method according to claim 3, characterized in that: Specifically include: Ultrasonic mixing of polytetrafluoroethylene emulsion and water to form polytetrafluoroethylene dispersion; Adding the polymerization monomer to the polytetrafluoroethylene dispersion, and dropping an initiator at 55-80° C. and stirring for 4-10 hours to obtain surface-activated polytetrafluoroethylene; Furthermore, the surface activated polytetrafluoroethylene is mixed with the two-dimensional sheet material and stirred at 25-60° C. for 12-36 hours to obtain core-shell structured hybrid particles.
5. The preparation method according to claim 4, characterized in that: The polymerizable monomers include any one or more of methyl methacrylate, glycidyl methacrylate, acrylamide, styrene, ethyl acrylate, divinylbenzene, vinyl methoxysilane, and γ-methacryloxypropyltrimethoxysilane; and / or, the initiator comprises potassium sulfate and / or sodium persulfate; And / or, the groups on the surface of the surface activated polytetrafluoroethylene include any one or more combinations of hydroxyl, carboxyl, amino, benzene ring, carbonyl, ester, and epoxy groups; and / or, the content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 3-7 wt.%; And / or, the mass ratio of the polytetrafluoroethylene dispersion to the polymerization monomer is 1:(1.5-3); And / or, the mass ratio of the surface activated polytetrafluoroethylene to the two-dimensional sheet material is (3-5):
1.
6. A method for preparing an anti-corrosion and wear-resistant coating, characterized in that: include: The core-shell structure hybrid particles are mixed evenly with a water-based resin system, and then the obtained material is applied to the surface of a metal substrate for curing to obtain an anti-corrosion and wear-resistant coating; Wherein, the core-shell structure hybrid particles include the core-shell structure hybrid particles described in claim 1 or 2.
7. The preparation method according to claim 6, characterized in that: The curing temperature is 30-50°C; And / or, the curing treatment time is 60 to 90 hours; And / or, the mass ratio of the core-shell structure hybrid particles to the aqueous resin system is (0.2-2):
100.
8. The preparation method according to claim 6, characterized in that: The water-based resin system comprises a first component and a second component; wherein the first component comprises a water-based resin and a dispersion, and the second component comprises a water-based curing agent and a defoaming agent; And / or, the metal substrate includes any one of carbon steel, stainless steel, aluminum alloy, and titanium alloy; And / or, the thickness of the anti-corrosion and wear-resistant coating is 20-100 μm.
9. The anticorrosion and wear-resistant coating prepared by the preparation method according to any one of claims 6 to 8.
10. Use of the core-shell structure hybrid particles according to any one of claims 1 to 2 or the anti-corrosion and wear-resistant coating according to claim 9 in the field of protection of marine engineering equipment serving in extreme deep-sea environments.
Citation Information
Patent Citations
Polytetrafluoroethylene-based core-shell type mesoporous composite material, preparation method thereof, oil-immersed mesoporous composite material and application
CN112961536A
Two-dimensional nano-hybrid composite anticorrosive coating filler as well as preparation method and application thereof
CN113308139A
Water-based anticorrosive coating applied to deep sea environment as well as preparation method and application of water-based anticorrosive coating
CN113549386A
Water-based anticorrosive coating based on graphene oxide and preparation method therefor
WO2021068506A1
Cited By
Wear-resistant coating for color-coated aluminum plate strip and preparation method of wear-resistant coating
CN121759083A
